PENGARUH HUBUNGAN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI DENGAN MOTIVASI KERJA SEBAGAI VARIBEL MODERATING - Ambarini, Ernawati & (Universitas Slamet Riyadi, 2010)
ABSTRACT The aims of this research is to examine the effect of: (1) The working relationship to performance, (2) work environment on performance, (4) Work motivation moderate the influence of the working relationship and work environment on staff performance Karanganyar District Personnel Agency. Employee population of the District Personnel Agency Karanganyar numbered 54 people. Conclusion The results of the study: (1) The hypothesis that says: